Synthesis and assessment of a maleimide functionalized BF2 azadipyrromethene near-infrared fluorochrome. Issue 93 (1st October 2015) - Wu, Dan; Cheung, Shane; Devocelle, Marc; Zhang, Li-Jun; Chen, Zhi-Long; O'Shea, Donal F.
Abstract : Aqueous soluble NIR-AZA fluorochrome which undergoes rapid rt bio-conjugations via thiol addition for in vitro and in vivo imaging. Abstract : The first water soluble maleimide bearing NIR BF2 -azadipyrromethene (NIR-AZA) fluorochrome has been synthesised which is capable of rapid thiol conjugations in water with peptides such as glutathione, the cell penetrating peptide (CPP) C(β-A)SKKKKTKV-NH2 and a thiol substituted cRGD. NIR fluorescence imaging showed rapid cellular delivery of the CPP conjugate and effective in vivo tumour localization for the cRGD conjugate.